Environmental issues of lighting and prospects of energysaving LED lighting systems with combined power supply - Yuriy Kolomzarov; Vitaliy Kostylyov; Viktor Sorokin; Yurii Nikolaenko; Demyd Pekur; Vasyl Kornaga; Roman Korkishko (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
Using LED technologies to create a comfortable light environment for human life and work can help reduce electricity consumption while maintaining, and usually improving, the energy and spectral parameters of lighting systems. At the same time, LED lighting systems for residential and industrial buildings are usually powered by electricity generated mainly by thermal power plants. Such plants mostly use fossil fuels and their combustion leads to environmental pollution. The article proposes the concept of a lighting system, which allows improving the ecology by reducing the energy consumption of lighting systems through the use of renewable energy sources. The proposed operation algorithm of the system for power supply control of LED light sources allows selecting the most appropriate energy sources in real time, thus making it possible to increase the luminous efficiency of the lamp by at least 20% when using industrial element base. This design can help to move away from traditional energy storage systems (batteries), which significantly increases the service life of such systems, their reliability and environmental safety. Placing photovoltaic converters in close proximity to the consumer (on the roofs and facades of buildings) ensures a decrease in ohmic losses and creates favorable conditions for using solar energy to light residential and industrial premises with LED lamps, which can significantly increase the economic and energy efficiency of such systems.